Doxorubicin-encapsulated Albumin liposomes with acoustic triggering for cancer treatment - Farooq, Afifa (2019)
A Master of Science thesis in Biomedical Engineering by Afifa Farooq entitled, “Doxorubicin-encapsulated Albumin liposomes with acoustic triggering for cancer treatment”, submitted in May 2019. Thesis advisor is Dr. Ghaleb Husseini. Soft and hard copy available.